2021
DOI: 10.1002/jssc.202100523
|View full text |Cite
|
Sign up to set email alerts
|

Titanium dioxide‐functionalized dendritic mesoporous silica nanoparticles for highly selective isolation of phosphoproteins

Abstract: Selective isolation of phosphoproteins is of great significance in biological applications. Herein, titanium dioxide‐functionalized dendritic mesoporous silica nanoparticles are prepared via a post‐grafting method for selective capture of phosphoproteins. The fabricated nanoparticles possess a unique central‐radial pore structure with a surface area of 666.66 m2/g and a pore size of 22.2 nm. The high‐binding affinity of TiO2 with the phosphate groups facilitates the selective adsorption of phosphoproteins. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Shu et al reported that an amino-terminated dendritic MSN that has a flower-type silica architecture shows a highly accessible central-radial pore and surface area, which play an important role in its superior adsorption capacity toward low-density lipoproteins. 44 45 and MSNs with methylation modification can capture membrane proteins efficiently. 46 Affinity chromatography is an efficient protein separation method based on the interaction between specific immobilized ligands and target proteins, and nucleic-acid aptamers are promising affinity ligands in affinity chromatography.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shu et al reported that an amino-terminated dendritic MSN that has a flower-type silica architecture shows a highly accessible central-radial pore and surface area, which play an important role in its superior adsorption capacity toward low-density lipoproteins. 44 45 and MSNs with methylation modification can capture membrane proteins efficiently. 46 Affinity chromatography is an efficient protein separation method based on the interaction between specific immobilized ligands and target proteins, and nucleic-acid aptamers are promising affinity ligands in affinity chromatography.…”
Section: Introductionmentioning
confidence: 99%
“…Qiao et al prepared titanium dioxide-functionalized dendritic MSNs for selective capture of phosphoproteins. The open central-radial pore structure endows the dendritic MSNs with excellent adsorption performance toward phosphoproteins by providing abundant accessible affinity sites, and MSNs with methylation modification can capture membrane proteins efficiently . Affinity chromatography is an efficient protein separation method based on the interaction between specific immobilized ligands and target proteins, and nucleic-acid aptamers are promising affinity ligands in affinity chromatography. , dsDNA is a natural substrate for the MutY protein.…”
Section: Introductionmentioning
confidence: 99%
“…For glycoprotein/glycopeptide enrichment, lectin-afnity chromatography [12], boronic acid afnity materials [13], hydrazide chemistry [14], and hydrophilic interaction liquid chromatography (HILIC) [15] were developed and widely used ascribing to the advantages of easy operation and universality. As for phosphoprotein/ phosphopeptides enrichment, immobilized metal afnity chromatography (IMAC) and metal oxide afnity chromatography (MOAC) were the two main enrichment strategies due to their merits of low cost and ease-of-use [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…As for phosphoprotein enrichment, there are mainly four strategies, including immunoaffinity [7], chemical derivatization [8,9], IEC [10], and affinity materials [11][12][13]. Among them, affinity materials possessed the merits of low cost, universality, and negligible effect on the structural integrity of phosphorylated groups [14].…”
Section: Introductionmentioning
confidence: 99%